The use of granulocyte colony-stimulating factors in the management of breast cancer patients - Bałata, Anna; Szombara, Ewa; Nowecki, Zbigniew I.; Pogoda, Katarzyna (Frontiers in Oncology, 2025)
The dynamic development of oncology poses new challenges to health care practitioners (HCPs), related to the introduction of modern targeted therapies, immunotherapies, or new chemotherapy regimens. The previous treatment algorithm for neutropenia and febrile neutropenia have significantly reduced the frequency of these complications in long-term therapies. Currently, breast cancer (BC) treatment is also based on the use of modern therapies, showing different toxicity profile. This article discusses the role of granulocyte colony-stimulating factors (G-CSFs) in well-known and new therapies used in the treatment of breast cancer patients. The factors influencing the development of hematological complications such as neutropenia and febrile neutropenia were presented. An important aspect of the assessment of patients at increased risk of therapy-induced toxicity was discussed with highlighting the fact that the treatment regimen is not the only factor influencing the development of adverse events (AEs). The aim of the study is to consolidate recommendations for the primary and secondary prevention of neutropenia and febrile neutropenia and related improvement of treatment outcomes in patients with BC.